2009
DOI: 10.5539/ijbm.v4n11p11
|View full text |Cite
|
Sign up to set email alerts
|

The Differences in Job Characteristics, Job Satisfaction, and Organizational Commitment of Taiwanese Expatriates Working

Abstract: With a population of 1.2 billion, mainland China has become a major target country for many foreign companies looking to expand their businesses because of its inexpensive labor and large market. In 2009, there were 77,642 companies from Taiwan operating in mainland China with fiscal expenditures exceeding US $47.77 billion dollars. If Taiwan's foreign direct investment (FDI) and offshore investment expenditures were included, Taiwan would have had the second largest FDI in mainland China. The purpose of this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…These job factors are needed to sustain and improve organizational commitment among teachers. The result of this study was supported with Huang and Hsiao [39] and Liu and Norcio [40] in which they stated that job factor is a strong predictor towards affective commitment. Furthermore, Lee and Ashforth also stated that emotional, high workload, lack of autonomy and intent to turnover may decrease organizational commitment among employees [41].…”
Section: Results Of Structural Equation Modelingsupporting
confidence: 79%
See 1 more Smart Citation
“…These job factors are needed to sustain and improve organizational commitment among teachers. The result of this study was supported with Huang and Hsiao [39] and Liu and Norcio [40] in which they stated that job factor is a strong predictor towards affective commitment. Furthermore, Lee and Ashforth also stated that emotional, high workload, lack of autonomy and intent to turnover may decrease organizational commitment among employees [41].…”
Section: Results Of Structural Equation Modelingsupporting
confidence: 79%
“…DaudT reportedT thatT growthT playsT anT importantT roleT toT organizationalT commitment,T whereT mostT ofT theT respondentsT inT theT interviewT sessionT mentionedT thatT appreciation,T recognitionT andT rewardT forT employeeT contributionsT canT increaseT commitmentT toT theT organizationT [32].T WengT etT al.T inT theirT surveyT alsoT foundT thatT growthT hasT aT positiveT relationshipT withT organizationalT commitmentT amongT workersT inT China,T inT whichT theirT studyT wasT focusedT onT howT growthT canT beT usedT inT managingT organizationalT commitmentT [33].T BarbierT etT al.T mentionedT thatT performanceT expectationT mayT contributeT toT positiveT effect,T whereT itT drivesT employeesT toT increaseT theirT workT effortT andT achieveT organizationalT expectationT [34].T ThisT alsoT canT contributeT toT improveT organizationalT commitmentT amongT employees.T Autonomy,T meaningfulT work,T taskT varietyT andT workloadT balanceT areT clusteredT underT jobT factors.T WrzesniewskiT etT al.T statedT thatT individualsT whoT haveT aT meaningfulT workT areT moreT likelyT toT seeT theirT workT asT aT careerT butT alsoT focusT onT organizationalT developmentT [35].T Geldenhuys,T TabaT andT VenterT inT theirT studyT onT 415T workersT inT SouthT AfricaT foundT thatT meaningfulT workT hasT aT significantT effectT onT organizationalT commitmentT [36].T WhenT employeesT obtainT meaningfulT work,T itT willT indirectlyT increaseT organizationalT commitment.T OzturkT mentionedT thatT autonomy,T feedbackT andT taskT varietyT canT influenceT andT helpT employeesT monitorT theirT behaviorT whichT isT alsoT expressedT asT aT senseT ofT personalT controlT asT wellT asT aT senseT ofT responsibilityT [37].T WhenT employeesT haveT aT senseT ofT responsibility,T theyT tendT toT helpT theirT organizationsT andT performT well. EbyT etT al.T alsoT foundT thatT autonomyT andT feedbackT haveT aT positiveT relationshipT withT affectiveT commitmentT [38].T HuangT andT HsiaoT mentionedT thatT jobT factorsT areT strongT predictorsT towardsT affectiveT componentT [39].T TheirT studyT wasT alsoT supportedT byT LiuT andT NorcioT whoT foundT thatT jobT factorsT haveT significantT relationshipT withT affectiveT componentT [40].T ApartT fromT that,T LeeT andT AshforthT concludedT thatT emotions,T workload,T lackT ofT autonomyT andT intentT toT turnoverT mayT decreaseT organizationalT commitmentT amongT workersT [41].T DeweT statedT thatT workloadT isT aT commonT stressT inT workplaceT [42].T TheseT resultsT wereT consistentT withT ZigarmiT etT al. 'sT studyT whichT foundT thatT workloadT balanceT canT affectT organizationalT behaviorT suchT asT organizationalT commitmentT [43].T Furthermore,T taskT varietyT isT alsoT relatedT toT organizationalT commitmentT [44].T Finally,T individualT factorsT consistT ofT connectednessT withT colleagues,T connectednessT withT leader,T collaborationT andT feedbackT [22].T AnsariT etT al.T inT theirT studyT reportedT thatT fairnessT inT relationshipT amongT employeesT wasT associatedT withT allT componentsT ofT organ...…”
Section: Relationshipt Betweent Workt Passiont Andt Organizationalt Cmentioning
confidence: 97%
“…For example, Weaver's work (1980) shows the general tendency for white-collar workers to have higher job satisfaction than blue-collar workers. Furthermore, Stepina (1985) found a consistent positive relationship between position level and job satisfaction, and Liu (2008) found higher reported job satisfaction for executives and major professionals than administrative, sales, clerical workers, machine operators, minor professionals, technicians, or semiskilled workers. Additionally, Kawada and Otsuka (2011) reported that compared to clerical workers, blue-collar unskilled manual workers reported significantly higher levels of job dissatisfaction.…”
Section: Job Type and Autonomy-job Satisfaction Relationshipmentioning
confidence: 97%
“…They explained that those with higher formal degrees in education have jobs that involve the possibility of using a wider range of skills but those with less education have jobs with more repetitive tasks and limited skill variety. Liu's (2008) dissertation involving Taiwanese expatriate workers in China found employees in jobs categorized as higher executives and major professionals reported higher levels of skill variety and autonomy than minor professionals, administrative personnel, sales or clerical employees, technicians, machine operators, or semiskilled workers. Liu (2008) also found higher reported job satisfaction as well as OC for higher executives and major professionals than administrative, sales, clerical workers, machine operators, minor professionals, technicians, or semiskilled workers, suggesting the moderation of job type between job characteristics and worker outcomes predicted by our study.…”
Section: Job Type Moderating Skill Variety-worker Outcome Relationshipsmentioning
confidence: 99%
“…The normative obligation is defined as the commit employee, and his other to stay in the organization [46]. While another researchers defined normative commitment as responsibility employee towards his that is characteristics by believing that loyalty is a normal case absorbing the fact that he must stay in organization until retired, and the believing that he must sacrificed for the organization [47].…”
Section:  Normative Commitmentmentioning
confidence: 99%